Becoming a Sustainable of Da'wah Organization in Crisis Era: Experience from Rumah Tahfiz in Bengkulu - M. Ridho Syabibi; Ashadi Cahyadi; Netta Agusti (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to explore the management of da'wah organizations generally relies on an unlimited donation mechanism. The non-profit pattern makes it possible for organizations to experience financial risk in times of crisis. This paper reveals the efforts made by the Rumah Tahfiz Impian (RTI) in Bengkulu City to continue to be sustainable during Covid-19. Field data was collected through in-depth interviews with ten informants; non-participant observations were made several times to obtain additional evidence and documentation that was considered supportive. All data is tabulated and analyzed using coding, categorization, and thematic systems. Our panel found that cost-sharing was the key to RTI's success in getting out of the crisis. Inconsistencies in donor donations are still resolved by dividing the daily operational burden among the students' parents and the community around the environment. Several efforts were made, such as scheduling pickets between side dishes and vegetables, rice or primary food donations, and money. This finding provides insight into Rumah Tahfiz which has cases of opening institutions that need more planning and management skills. Research with the same focus but for different cultural backgrounds of society needs to be carried out in the future